Interactive effects of wildfire and climate on permafrost degradation in Alaskan lowland forests. Issue 8 (18th August 2015) - Brown, Dana R. N.; Jorgenson, M. Torre; Douglas, Thomas A.; Romanovsky, Vladimir E.; Kielland, Knut; Hiemstra, Christopher; Euskirchen, Eugenie S.; Ruess, Roger W.
Abstract: We examined the effects of fire disturbance on permafrost degradation and thaw settlement across a series of wildfires (from ~1930 to 2010) in the forested areas of collapse‐scar bog complexes in the Tanana Flats lowland of interior Alaska. Field measurements were combined with numerical modeling of soil thermal dynamics to assess the roles of fire severity and climate history in postfire permafrost dynamics. Field‐based calculations of potential thaw settlement following the loss of remaining ice‐rich permafrost averaged 0.6 m. This subsidence would cause the surface elevations of forests to drop on average 0.1 m below the surface water level of adjacent collapse‐scar features. Up to 0.5 m of thaw settlement was documented after recent fires, causing water impoundment and further thawing along forest margins. Substantial heterogeneity in soil properties (organic layer thickness, texture, moisture, and ice content) was attributed to differing site histories, which resulted in distinct soil thermal regimes by soil type. Model simulations showed increasing vulnerability of permafrost to deep thawing and thaw settlement with increased fire severity (i.e., reduced organic layer thickness). However, the thresholds of fire severity that triggered permafrost destabilization varied temporally in response to climate. Simulated permafrost dynamics underscore the importance of multiyear to multidecadal fluctuations in air temperature and snow depth in mediating the effects of fire on permafrost. Our results suggest that permafrost is becoming increasingly vulnerable to substantial thaw and collapse after moderate to high‐severity fire, and the ability of permafrost to recover is diminishing as the climate continues to warm. Key Points: Lowland forests are susceptible to ecosystem change if ice‐rich permafrost thaws Fire can cause permafrost thaw, thaw settlement, and water impoundment Permafrost is now more vulnerable to thawing after fire due to climate warming